Formação, educação física e inclusão : compreendendo os processos inclusivos - Souza, Fabricio Amaral de (2013)
This dissertation aims to present and analyze the inclusive pedagogic practice experimented by the Physical Education teachers at school through their career, with the aim to contribute to the development of Education in an inclusive perspective, in an action of continuing formation. The extension project entitled Continuing Formation of Physical Education Teachers for an Inclusive Education was the chosen strategy for the creation of a study group names Group of Operative Formation. The action of continuing formation was realized in the period between July and December 2011, in sixteen weekly encounters totalizing 90 hours of work load. Four teachers of Municipal Office of Education of Vitória (Espírito Santo, Brazil) participated to the formation activities. The study is based on research-action elements, using as instruments and procedures for the production of data: narrative, field diary, the memorial and the interview. Three orienting categories were identified from the analysis of the collected data: a) collective work as a possibility for inclusion; b) showing potential ways for the development of inclusion pratices, focussing on autism; c) teacher's perception of the formation proposal experimented in the study group. Realized analysis reveal that the formative proposal positively contributes as a active instrument, in the formation process of teachers in elementary education, in the perspective of inclusion. Therefore, it is evaluated as an interesting instrument for alternative methodologies to be used in formation networks of continuous formation programs. Moreover, the proposal promotes moments for reflective pratice, representing good opportunities for the teachers to appropriate theories able to contribute to the elaboration of their lessons.